c.3 - Pande, Suchi (New Delhi, 2008)
This Primer is designed to help seekers of information, its custodians and RTI appellate authorities. Through a question answer format it introduces the lay reader to the RTI ACT and its implementation, its use and function as well as details of how information can be accessed and appeals filed. The Primers also highlights the rights and duties of public information officers and public authority. Also includes sample application form and appeal formats.
Keywords: Right to Information Act 2005